Incorporating mean-field velocity difference in a continuum macroscopic traffic flow model for adverse road conditions - Gabriel Obed Fosu; Dickson Anokye; Albert Adu-Sackey; Bright Emmanuel Owusu (Mathematics in Applied Sciences and Engineering)
In developing countries, the quality of driving infrastructure, specifically road conditions, is often suboptimal, presenting challenges and limitations for motorists. However, current traffic flow models have limitations in addressing problems caused by poor road networks. To address this issue, a new macroscopic traffic flow model has been proposed in this study that considers mean-field velocity differences on roads with suboptimal conditions. A thorough model derivation of this new macroscopic traffic flow model is presented. The study establishes crucial stability conditions, providing profound insights into traffic dynamics across diverse scenarios. Numerical simulations are presented to demonstrate the model's ability to capture shock waves, rarefaction waves, and local cluster effects. The study results offer new insights into traffic dynamics in adverse road conditions and enforce the need to enhance road infrastructure to alleviate congestion and enhance road safety.